Psychoanalysis with children online? Reflections on care during the pandemic - Nogueira, Tiago Sanches (Clinical Styles. The Journal on the vicissitudes of childhood, 2021)
This article examines the vicissitudes of clinical care provided to a child during the pandemic. It is an analysis conducted online in the first few months of confinement that required some psychoanalyst from the psychoanalyst to make the treatment feasible. The establishment of teaching on how to draw eyes, as well as working with moving photographs (stop motion), emerged as alternatives for the boy to master the obscene look of the Other. At the end, the discussion on how to give online work led us to the realization that it found the occurrence of a kind of suture what in film theory is called shot and reverse shot.